Vanadium induced impairment of haem synthesis. Issue 10 (October 1989) - Missenard, C; Hansen, G; Kutter, D; Kremer, A
Abstract : Biochemical and haematological profiles of workers exposed to vanadium were compared with those of non-exposed age matched subjects. A significantly positive and dose related correlation between serum vanadium and zinc protoporphyrin (ZPP) was observed. Normal lead concentrations excluded this heavy metal as a possible cause. Inhibition of the reduction of Fe to Fe++ by vanadium is discussed as the possible cause of interference of vanadium with haem synthesis. Iron and iron binding capacity were found to be significantly lower and ferritin significantly higher in the population exposed to vanadium. Strong inter-individual variations do not allow an explanation of this interference with iron metabolism.